The Influence of Workload and Organizational Culture on Teacher Performance at Hang Tuah Belawan High School - Leony Hoki; Irwadi Irwadi; Sheila Syntia (Digital Innovation : International Journal of Management, 2024)
This research identified the influence of workload and organizational culture on teacher performance at Hang Tuah Belawan High School. Workload and organizational culture are two important factors that can influence the quality of teacher performance. The research method used is a quantitative method with data collection techniques through questionnaires distributed to teachers at Hang Tuah Belawan High School. The research results show that partially workload has a negative and significant influence on teacher performance at Hang Tuah Belawan High School. On the other hand, organizational culture partially has a positive and significant influence on teacher performance at Hang Tuah Belawan High School. Furthermore, simultaneously workload and organizational culture have a significant influence on teacher performance at Hang Tuah Belawan High School. Based on the results of this research, it can be recommended that school management manage teacher workload more effectively and create and maintain a positive and supportive organizational culture. In this way, teacher performance can be improved, which will ultimately improve the quality of education at Hang Tuah Belawan High School.